Respuesta :

Answer:

x-(-1)=6

-x=6

-x/-1 6/-1

x=-6

Answer:

Therefore, the solution of the system of equations will be:

[tex]x=5,\:y=-1[/tex]

Step-by-step explanation:

Given the system of equations

[tex]x-y=6;\:y=-1[/tex]

solving

[tex]\begin{bmatrix}x-y=6\\ y=-1\end{bmatrix}[/tex]

[tex]\mathrm{Subsititute\:}y=-1[/tex]

[tex]\begin{bmatrix}x-\left(-1\right)=6\end{bmatrix}[/tex]

[tex]\begin{bmatrix}x+1=6\end{bmatrix}[/tex]

Isolate x for [tex]x+1=6[/tex]

[tex]x+1=6[/tex]

[tex]x=5[/tex]

Therefore, the solution of the system of equations will be:

[tex]x=5,\:y=-1[/tex]